PENGARUH PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN MASYARAKAT TERHADAP KEMISKINAN DI PROVINSI D.I. YOGYAKARTA, 2002-2009 - , Meitri Pafrida; , Tri Widodo, M. Ec.Dev., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to determine the development of poverty, whether economic growth increases or decreases income inequality, and to determine the effect of of growth and income inequality on poverty. Then, it would identify whether economic growth in the province of DIY has been pro-poor. The data used is secondary data. It consists of GDP per capita, the Gini index, and the poverty rate covers all districts in D.I. Yogyakarta Province, the period of 2002-2009. The methods used are descriptive analysis of poverty trends and regression analysis with fixed effect model-cross section SUR weighted or pooled EGLS (cross section-SUR). The results showed that poverty in the province of Yogyakarta, showed a declining trend, but there are two districts that showed an increasing trend. Regression model showed that economic growth is negatively affected by income inequality elasticity value of 0.45. Economic growth was also negatively affect the net elasticity of poverty so that poverty to economic growth (0.39) is greater than its gross elasticity (0.36). Value of Pro-poor growth index (PPGI) of 1.075 indicates that economic growth in Yogyakarta Province is very pro-poor.